2018
DOI: 10.3390/nu10030350
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids and Insulin Resistance: Focus on the Regulation of Mitochondria and Endoplasmic Reticulum Stress

Abstract: Mitochondrial dysfunction and endoplasmic reticulum (ER) stress have been suggested to play a key role in insulin resistance development. Reactive oxygen species (ROS) production and lipid accumulation due to mitochondrial dysfunction seemed to be important mechanisms leading to cellular insulin resistance. Moreover, mitochondria are functionally and structurally linked to ER, which undergoes stress in conditions of chronic overnutrition, activating the unfolded protein response, which in turn activates the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(125 citation statements)
references
References 124 publications
1
123
0
1
Order By: Relevance
“…Like, the study by Marilena Lepretti et al showed that dietary omega 3 polyunsaturated fatty acids were able to recover insulin resistance by modulating ROS production and endoplasmic reticulum stress. 37 Similarly, Hoehn et al also showed that manganese(III) tetrakis (4-benzoic acid) porphyrin, a broad-spectrum antioxidant, was capable of scavenging not only O 2 À and H 2 O 2 , but also reactive nitrogen species, and improved glucose tolerance in HFD-fed C57BL/6JSlc mice. 38 Thus, it was important to highlight that R3G and R4G were also able to reduce cellular ROS levels in insulin-resistant HepG2 cells.…”
Section: R3g and R4g Regulated Phosphorylation Of Irs-1 And Ampk In Imentioning
confidence: 95%
“…Like, the study by Marilena Lepretti et al showed that dietary omega 3 polyunsaturated fatty acids were able to recover insulin resistance by modulating ROS production and endoplasmic reticulum stress. 37 Similarly, Hoehn et al also showed that manganese(III) tetrakis (4-benzoic acid) porphyrin, a broad-spectrum antioxidant, was capable of scavenging not only O 2 À and H 2 O 2 , but also reactive nitrogen species, and improved glucose tolerance in HFD-fed C57BL/6JSlc mice. 38 Thus, it was important to highlight that R3G and R4G were also able to reduce cellular ROS levels in insulin-resistant HepG2 cells.…”
Section: R3g and R4g Regulated Phosphorylation Of Irs-1 And Ampk In Imentioning
confidence: 95%
“…This effect was probably related to an increased expression of the mitochondrial uncoupling protein 3 (UCP3) [119]. Moreover, the dietary supplementation with omega 3 FA increased CPT-1 expression and activity in rat skeletal muscle, indicating an increase in FA β-oxidation ( Figure 2) [77,120]. Thus, omega 3 FA could increase lipid oxidation to limit or prevent the production of lipotoxic mediators implicated in the development of CVD and sarcopenia.…”
Section: Omega 3 and Muscle Metabolismmentioning
confidence: 99%
“…The decline in mitochondrial FA β-oxidation could also contribute to ectopic lipid accumulation and the RA-related increase in adiposity and metabolic disorders. These events will contribute to further aggravate all the mentioned alterations, amplifying the accumulation of ectopic fat and the progression of anabolic resistance [77,78]. However, the links between mitochondrial dysfunctions in skeletal muscle, lipitoxicity, IL-17 and RA remain unexplored.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Preclinical studies have demonstrated that a flaxseed oil diet, another natural source of omega-3 fatty acid, does increase the expression of G-protein-coupled receptor 120 (GPR120), a receptor of omega-3, but not GPR40 [194] (see Table 2). Remarkably, omega-3 PUFAs suppress ER stress in adipocytes by AMPK activation, and resolvin D1, a family derived from eicosapentaenoic and docosahexaenoic acids, attenuates ER stress-induced apoptosis and decreases caspase-3 activity [195].…”
Section: Polyphenols: Anthocyanins and Resveratrolmentioning
confidence: 99%